Elevated temperature ablation mechanisms of Cu@rGO/CuW nanocomposites under oxyacetylene torch flame - Longlong Dong; Yan Tang; Xiang Li; Shuang Zhang; Wei Zhang; Yongqing Fu; Ahmed Elmarakbi; Yusheng Zhang (Journal of Materials Research and Technology, 2023)
Copper-tungsten (CuW) composites have been explored in throat lining applications for the rudders and nozzles in the rocket motors, hence it is crucial to investigate their high-temperature ablation behaviors and the corresponding failure mechanisms. Herein, xCu modified reduced graphene oxide reinforced CuW (named as Cu@rGO/CuW) composites (x = 0, 1, 3 and 5 wt%) were fabricated using spark plasma sintering to evaluate their ablation resistances under an oxyacetylene torch flame and to improve their high temperature ablation resistance with in-situ formed tungsten carbides (WC and W2C) during sintering. The composite's surface after ablation can be clearly divided into two regions, i.e., central erosion region and edge transitional region. The ablation products were mainly consisted of WO3, CuWO4 and WC phases. The mass ablation rate and linear ablation rate of 3 wt% Cu@rGO/CuW composite were 0.015 g/s and 0.0023 mm/s, which are 0.25 and 0.3 times smaller than those of the monolithic CuW alloy, respectively. The superior elevated temperature ablation resistance of the composites was attributed to transpiration cooling of Cu and WO3, heat consumptions of the remained Cu@rGO with a high thermal conductivity, and in-situ formation of WC or W2C particles with high melting points. The key failure mechanisms of the Cu@rGO/CuW composites during ablation process with high temperature are thermo-chemical oxidation and thermo-mechanical ablation of oxides such as WO3, Cu2O and CuWO4.